Locally advanced basal cell carcinoma in real life: Analysis of a cohort of 452 patients treated with systemic therapy from the CARADERM database - F. Herms; M. Djermane; M. Beylot-Barry; C. Chaffaut; S. Dalac; O. Dereure; J.J. Grob; L. Mortier; J. Lambert; N. Basset-Seguin (EJC Skin Cancer)
Background: Locally advanced basal cell carcinoma (LaBCC) is a challenging condition. The European Association for Dermato-Oncology (EADO) suggested the classification of laBCC into 5 groups. In this study, we aimed to describe patient characteristics and treatment responses in a large cohort of real-life laBCC patients treated with systemic therapy from a nationwide French database (CARADERM). Methods: LaBCC patients from the CARADERM database were analyzed. Patient demographic data, tumor characteristics, response to treatment and reasons for discontinuation, if applicable, were retrospectively collected. We allocated every patient to the corresponding group according to the EADO classification. Results: The cohort included 452 patients (median age of 77 years and 59 % male sex). LaBCC in the critical zone was the most common group (38 %). Therapeutic response to Hedgehog inhibitors after 10 months of follow-up was evaluated in 353 patients. Complete (CR) and partial response were 39 % and 49 %. Patients with common laBCC achieved CR more frequently (47 %) than patients with very advanced BCC (29 %). Among the 55 patients who achieved CR and stopped treatment, 25 relapsed. The cumulative incidence of relapse at 18 months was 64.2 % (95 % confidence interval (95CI) = 44.6;78.4). The treatment discontinuation rate at 2 years was 88.1 % (95CI = 83.8;91.3). Sonidegib appeared more tolerable. Conclusion: In this largest ever real-life laBCC cohort, tumors were more frequently involving critical areas. The response to treatment was not significantly different between clinical groups, although patients with very advanced BCC had a lower CR rate. The overall efficacy was comparable to that of pivotal trials.